Design and Analysis of Modified Diode Rectifier Circuit Suitable for Piezoelectric Energy Harvester for Biomedical Applications - S. Dhayabarasivam, S; Jayanthi, K; Pragatheeswaran, Gouthame (International Journal of Engineering and Technology, 2018)
Nowadays renewable energy sources play a significant role in the energy harvesting. For the past decade various energy harvesting methods have been discussed by researchers for capturing the energy from different sources. From the survey, one of the most prominent methods is the use of piezoelectric transducers for harvesting the energy. It is known that piezoelectric energy harvesting is the easiest method of energy harvesting from the various sources available such as human walking, dancing etc. Therefore this method can be implemented in system for wide variety of applications. The piezoelectric transducer AC output is of very low voltage and power and hence insufficient to drive any electrical application. Most of the small scale electrical application generally runs on the DC voltage, therefore the AC voltage obtained from the piezo transducer vibration is rectified using rectifiers to generate DC voltage. Thus in this paper, a modified rectifier AC/DC converter with the combination of an inductor is placed in the rectifier, which enhances the voltage and power from the rectifier output. In order to enhance the voltage rating, a DC/DC converter has been added at the end of a rectifier circuit. From the simulation results the proposed circuit modified rectifier has improved the output voltage as well as output current by 10.19 volts and 0.1019 amps respectively for input voltage of 5V. When compared with conventional rectifier circuit.